Cognitive decline due to excess synaptic Zn2+ signaling in the hippocampus - Takeda, Atsushi (Frontiers in Aging Neuroscience, 2014)
Zinc is an essential component of physiological brain function. Vesicular zinc is released from glutamatergic (zincergic) neuron terminals and serves as a signal factor (Zn2+ signal) in both the intracellular (cytosol) compartment and the extracellular compartment. Synaptic Zn2+ signaling is dynamically linked to neurotransmission and is involved in processes of synaptic plasticity such as long-term potentiation (LTP) and cognitive activity. On the other hand, the activity of the hypothalamic-pituitary-adrenal (HPA) axis, i.e., glucocorticoid secretion, which can potentiate glutamatergic neuron activity, is linked to cognitive function. HPA axis activity modifies synaptic Zn2+ dynamics at zincergic synapses. An increase in HPA axis activity, which occurs after exposure to stress, may induce excess intracellular Zn2+ signaling in the hippocampus, followed by hippocampus-dependent memory deficit. Excessive excitation of zincergic neurons in the hippocampus can contribute to cognitive decline under stressful and/or pathological conditions. This paper provides an overview of the 'Hypothesis and Theory' of Zn2+-mediated modification of cognitive activity.